2012
DOI: 10.7314/apjcp.2012.13.8.3931
|View full text |Cite
|
Sign up to set email alerts
|

Variants on ESR1 and their Association with Prostate Cancer Risk: A Meta-analysis

Abstract: Background: Epidemiological studies evaluating the association of two variants rs9340799 and rs2234693 on estrogen receptor 1 (ESR1) with prostate risk have generated inconsistent results. Methods: A meta-analysis was here conducted to systematically evaluate the relationship of these two variants with prostate cancer susceptibility. Results: For rs9340799, heterozygosity of T/C carriers showed a significant increased prostate cancer risk with a pooled odds ratio (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Remarkably, both sites of rs9340799 and rs2234693 have been widely studied in ESRα genetic polymorphisms [ 9 – 12 ], but ESRα rs9340799 or rs2234693 were independent of PC susceptibility because of quality and quantity limitations. The meta-analysis of ESRα rs9340799 and rs2234693 was firstly conducted by Ding [ 10 ] in 2012, indicating that rs9340799, not rs2234693, confered an elevated risk of PC. Gu's study [ 11 ] demonstrated that there was no significant difference between 4,884 case groups and 10,134 control groups in rs2234693 regardless of allele or other models (allele model, OR = 0.98; 95 % CI, 0.88–1.08; P = 0.685; dominant model, OR = 0.98; 95 % CI, 0.89–1.07; P = 0.685; recessive model, OR = 0.96; 95 % CI, 0.81–1.14; P = 0.657; homozygous model, OR = 0.96; 95 % CI, 0.77–1.19; P = 0.708; heterozygous model, OR = 0.96; 95 % CI, 0.81–1.13; P = 0.708, respectively).…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, both sites of rs9340799 and rs2234693 have been widely studied in ESRα genetic polymorphisms [ 9 – 12 ], but ESRα rs9340799 or rs2234693 were independent of PC susceptibility because of quality and quantity limitations. The meta-analysis of ESRα rs9340799 and rs2234693 was firstly conducted by Ding [ 10 ] in 2012, indicating that rs9340799, not rs2234693, confered an elevated risk of PC. Gu's study [ 11 ] demonstrated that there was no significant difference between 4,884 case groups and 10,134 control groups in rs2234693 regardless of allele or other models (allele model, OR = 0.98; 95 % CI, 0.88–1.08; P = 0.685; dominant model, OR = 0.98; 95 % CI, 0.89–1.07; P = 0.685; recessive model, OR = 0.96; 95 % CI, 0.81–1.14; P = 0.657; homozygous model, OR = 0.96; 95 % CI, 0.77–1.19; P = 0.708; heterozygous model, OR = 0.96; 95 % CI, 0.81–1.13; P = 0.708, respectively).…”
Section: Introductionmentioning
confidence: 99%